2022
DOI: 10.1007/s00726-022-03218-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of equilibria constants of arginine:glycine amidinotransferase (AGAT)-catalyzed reactions using concentrations of circulating amino acids

Abstract: Arginine:glycine amidinotransferase (AGAT) catalyzes mainly two reactions that generate 1) L-homoarginine (hArg) from L-arginine and L-lysine (Kharg) and 2) guanidinoacetate (GAA) and L-ornithine from L-arginine and glycine (Kgaa). Previously, we found that pharmacological treatment of Becker muscular dystrophy (BMD) patients with metformin or L-citrulline resulted in antidromic effects on serum hArg and GAA concentrations, seemingly acting as an inhibitor and effector of AGAT activity, respectively. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…It is noteworthy that metabolites belonging to creatine metabolism were the ones most related to biguanides, especially metformin and buformin, according to our results during structural, physicochemical, and binding comparisons. Recently, has authors have reported the competitive inhibition of AGAT by a metformin treatment (3 × 1500 mg daily for 6 weeks) in individuals with Becker muscular dystrophy, leading to reduced concentrations of guanidinoacetic acid in both serum and urine [ 55 ]. Remarkably, decreased renal and pancreatic AGAT activity, but not decreased mRNA expression, have been reported after creatine supplementation in rats, suggesting that creatine can be involved in a negative feedback regulation mechanism [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that metabolites belonging to creatine metabolism were the ones most related to biguanides, especially metformin and buformin, according to our results during structural, physicochemical, and binding comparisons. Recently, has authors have reported the competitive inhibition of AGAT by a metformin treatment (3 × 1500 mg daily for 6 weeks) in individuals with Becker muscular dystrophy, leading to reduced concentrations of guanidinoacetic acid in both serum and urine [ 55 ]. Remarkably, decreased renal and pancreatic AGAT activity, but not decreased mRNA expression, have been reported after creatine supplementation in rats, suggesting that creatine can be involved in a negative feedback regulation mechanism [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The urinary excretion rates of amino acids were corrected for the urinary excretion rate of creatinine, and these results are presented as µM analyte per mM creatinine. The equilibrium constant for the AGAT-catalyzed formation of GAA (i.e., K GAA ) from L-arginine (Arg) and glycine (Gly) was determined as described elsewhere (Tsikas 2022 ). The equilibrium constant for the AGAT-catalyzed formation of hArg (i.e., K harg ) from Arg and L-lysine (Lys) was determined similarly (Tsikas 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The equilibrium constant for the AGAT-catalyzed formation of GAA (i.e., K GAA ) from L-arginine (Arg) and glycine (Gly) was determined as described elsewhere (Tsikas 2022 ). The equilibrium constant for the AGAT-catalyzed formation of hArg (i.e., K harg ) from Arg and L-lysine (Lys) was determined similarly (Tsikas 2022 ). Because of co-elution and interconversion (Hanff et al 2019 ), the sum concentration for the following amino acids is reported: leucine and isoleucine (Leu + Ile), glutamate and glutamine (Glu + Gln), ornithine and citrulline (Orn + Cit), aspartate and asparagine (Asp + Asn).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation